Status of endodontic treatment and the correlations to the quality of root canal filling and coronal restoration - Pedro, Fabio M.; Marques, A. T.C.; Pereira, Thiago M.; Bandeca, Matheus C.; Lima, S. N.L.; Kuga, Milton C [UNESP]; Tonetto, Mateus R.; Semenoff-Segundo, Alex; Borges, Alvaro H. (Jaypee Brothers Medical Publishing, 2016)
Introduction: This cross-sectional study evaluated the prevalence and quality of root canal treatment in 1,977 digital radiological files. Materials and methods: Data were statistically analyzed using descriptive analysis, and the chi-square test was performed with a 5% significance level. Results: The mean age of the study population was 34.9 years. The endodontic treatment frequency was 6.14%, significantly higher in premolars. Adequate endodontic treatment was observed in 39.7% of analyzed cases. Molars were significantly more frequent with regard to inadequate filling quality. In 47.6% of cases, the filling's apical limit was classified as adequate, and there was a higher incidence of molars that were inadequate. Restorations were classified as adequate in 79.0% of cases, and molars were responsible for the highest frequency of inadequate restorations. The frequency of teeth with endodontic treatment that showed no periapical changes was 47.7%. There was no significant difference in the presence of periapical change according to gender. An increased presence of periapical change was observed with increasing age. The periapical lesions were observed in 45% of cases and related to inadequate filling quality. The apical limit was considered inadequate and related to periapical changes in 42% of cases. Periapical changes were present in 52% of cases, regardless of the quality of the filling and apical limit. Such changes were present in 42% of cases with adequate coronal restoration. Conclusion: It can be concluded that apical periodontitis (AP) is associated with the quality of endodontic treatment. The coronal restoration affects significantly the success rate of endodontic treatment. Clinical significance: The quality of the root filling and coronal restoration is closely related to periapical health.
Keywords: Endodontics; Panoramic; Radiography; Root canal preparation